Computed tomography features of discospondylitis in dogs - Sergio A. Gomes; Mike Targett; Mark Lowrie (Journal of Veterinary Internal Medicine, 2022)
Abstract Background Computed tomography (CT) findings of dogs with discospondylitis have not been widely described despite increased availability of this imaging modality. Objectives Describe the CT features of discospondylitis in a population of clinically affected dogs with discospondylitis diagnosed by magnetic resonance imaging (MRI). Animals Forty‐one dogs (63 affected discs) with MRI‐identified discospondylitis presented to a single referral hospital between 2012 and 2022. Methods Retrospective, single center, descriptive case series with analysis of MRI‐identified discospondylitis sites and concomitant CT imaging. Computed tomographic features of MRI‐affected sites including intervertebral disc space (IVDS), endplates, vertebral body, epidural space and paraspinal tissues were described. Results The most frequently found changes were: (1) endplate involvement (87.3%) most frequently bilateral (94.5%), with erosion (61.9%) and multifocal osteolysis (67.3%); (2) periosteal proliferation adjacent to the IVDS (73%) and spondylosis (66.7%); and (3) vertebral body involvement (66.7%) involving one‐third of the vertebra (85.7%) with multifocal osteolysis (73.5%). Other less prevalent features included an abnormal IVDS (narrowed or collapsed), sclerosis of the adjacent vertebral body or endplates, presence of disseminated idiopathic skeletal hyperostosis or vacuum artifact. Conclusions and Clinical Importance We determined that bilateral endplate erosion and periosteal proliferation were very common in dogs with discospondylitis. Careful evaluation of CT in all 3 planes (dorsal, sagittal, transverse) is necessary to identify an affected IVDS. These described CT features can aid in the diagnosis of discospondylitis in dogs but equivocal cases might still require MRI.